Sosialisasi dan Pelatihan Pentingnya Baca Tulis di Sekolah Dasar di Kabupaten Takalar - Angga Septiawan; Andi Haris Muhammad (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2022)
Education is the main thing that can be obtained formally or informally. In this era of globalization, the development of educational technology offers many conveniences in learning. One of them is the use of interesting and creative learning media such as the use of audio-visual technology that helps stimulate the senses of sight and hearing of students to improve their thinking and creativity in the learning and education process. Lakatong Village is one of the agricultural areas so it requires quality human resources for improvement in this field. However, in reality human resources in the village are still minimal, judging from the literacy skills of the children in the village. Therefore, this service activity was carried out to provide education and training to elementary school children at SDN 65 Pa'gannakkang to be able to read and write as the main step in increasing the HDI (Human Development Index). The methods used in this service are pre-test, material delivery, reading and writing practice, and post-test. Based on the results of the evaluation, it is known that the ability of 16 students has increased by 69% in writing and 37% in reading using audio-visual learning media. To further improve this, the role of parents and teachers is needed in the application of effective learning methods for children.